Pengaruh Program Sosialisasi Terhadap Pengetahuan Hukum Tentang Undang – Undang Informasi Dan Transaksi Elektronik Serta Pemberdayaan Masyarakat Desa Ranah Baru Dalam Mengakses Bantuan Hukum Dan Perlindungan Hukum, Kecamatan Kampar, Kabupaten Kampar - Ferawati, Ferawati; Bilbina, Andini Azerta; Widarsono, Anjani Syafira Arbie; Wijaya, Cornelia Navisa; Parendra, Dygta Arsya; Septiana, Elsa; Dewi, Putu Ayu Septiya Kusuma; Sianturi, Rachel Nissi; Situmorang, Ruben; Fainani, Widia (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2025)
The Community Service Program (KUKERTA) of Universitas Riau, implemented in Ranah Baru Village, Kampar District, represents a form of community engagement that integrates higher education with the real needs of society. The main focus of this program is to raise public legal awareness through legal literacy initiatives and education on the Law on Electronic Information and Transactions (UU ITE). The implementation of KUKERTA is not only intended as a means for students to apply the knowledge they have acquired but also as an effort to empower the community to better understand their legal rights and how to access legal aid easily and free of charge. The research methods employed include observation and interviews with village officials as well as local residents. These observations and interviews serve to provide a comprehensive overview of the challenges and obstacles faced by the community in understanding and accessing legal aid, particularly in the context of digital law as regulated by the Electronic Information and Transactions Law. Based on the data collected, the KUKERTA students developed three priority activities as the implementation of the program: sosialization on the importance of legal awareness and the right to obtain legal aid, distribution of posters to facilitate public access to legal aid services, and education on the limitations of digital communication in social media to ensure that the community, especially the younger generation, remains cautious and avoids potential legal violations. The findings indicate that legal awareness among the people of Ranah Baru Village remains relatively low, highlighting the importance of sustaining legal literacy programs to enhance community independence in protecting their rights. This article provides a significant contribution to the development of effective legal literacy models as an effort to empower communities in the rapidly growing digital era